Strategic Communication at Work : The Impact Paradigm - Lennard, Diane (Taylor and Francis, 2018)
"Strategic Communication at Work provides the reader with a practical approach to engaging in all types of communicationone on one, small groups, and large groupsto achieve intended results. The framework presented enables readers to make informed decisions that increase the effectiveness of their communication and enhance their credibility. Lennard presents the IMPACT ParadigmIntending, Messaging, Presence, Attending, Connecting, and Togetherin the first part of the book explaining the benefits of using a single framework for all strategic communication. The second part illustrates how to apply these principles and approach interactions with a purposeful mindset, express ideas congruently, and connect with others. The third part offers curated exercises for practicing communication skills, along with specific ways to integrate the paradigm into everyday communication interactions. The texts clear and practical approach will appeal to graduate students of business communication, as well as instructors and professionals interested in improving their communication skills."--Provided by publisher.